Superfluous glutamine synthetase activity in Chinese Hamster Ovary cells selected under glutamine limitation is growth limiting in glutamine-replete conditions and can be inhibited by serine - Maralingannavar, Vishwanathgouda; Parmar, Dharmeshkumar; Panchagnula, Venkateswarlu; Gadgil, Mugdha (Biotechnology Progress, 2019)
Passaging and expansion of animal cells in lean maintenance medium could result in periods of limitation of some nutrients. Over time, such stresses could possibly result in selection of cells with metabolic changes and contribute to heterogeneity. Here, we investigate whether selection of Chinese Hamster Ovary (CHO) cells under glutamine limitation results in changes in growth under glutamine-replete conditions. In glutamine-limiting medium, compared to control cells passaged in glutamine-rich medium, the selected cells showed higher glutamine synthetase (GS) activity and attained a higher peak viable cell density (PVCD). Surprisingly, in glutamine-replete conditions, selected cells still showed a higher GS activity but a lower PVCD. We show that in glutamine-replete medium, PVCD of selected cells was restored on (a) inhibition of GS activity with methionine sulfoximine, (b) supplementation of aspartate-without affecting GS activity, and (c) supplementation of serine, which is reported to inhibit GS in vitro. Consistent with the reported effect of serine, inhibition of GS activity was observed upon serine supplementation along with reduced growth of cells under glutamine-limiting conditions. The latter observation is important for the design of glutamine-free culture medium and feed used for GS-CHO and GS-NS0. In summary, we show that CHO cells selected under glutamine limitation have superfluous GS activity in glutamine-replete medium, which negatively affects their PVCD. This may be due to its effect on availability of aspartate which was the limiting nutrient for the growth of selected cells in glutamine-replete conditions.
Keywords: C-13 tracer analysis; CHO cells; glutamine limitation; Glutamine synthetase; GS-CHO; GS-NS0; selection under nutrient limitation; serine